THE PECULIARITIES OF WORD STRESS IN UZBEK, KARAKALPAK AND ENGLISH LANGUAGE - Elenora Khalmuratova (Journals Park Publishing, 2023)
As we know, word stress is the emphasis we place in a specific syllable of a word when pronouncing it. In English words that have more than one syllable, we usually don't pronounce every syllable with the same weight, so each syllable in a word can be stressed or unstressed. It is natural that word stress can be different from one another in other languages. Word stress, also called lexical stress, is an important suprasegmental feature in English because it determines so many other aspects of pronunciation. First, word stress determines which vowels in a word are pronounced with a clear vowel vs. schwa. The article is devoted to give data about the divergent peculiarities of word stress in three languages ( Uzbek, Karakalpak as well as English).
Keywords: stress, pitch, acoustic signs of a dynamic accent, the tension, the muscles of the speech organs, an accent, percussion, suprasegmental feature.